The Grubs - Watanabe Shiya (Nanyang Technological University, 2022)
The Grubs is a 8 min 2 sec short film Final Year Project (FYP) produced by GRUB STUDIOS. The short film was produced by Watanabe Shiya and Pearlyn Chang Xuan Qi, undergraduates from Nanyang Technological University, Wee Kim Wee School of Communication and Information (WKWSCI), under the supervision of Dr Kym Campbell.